Bat child$1 (Bs haunted house /s - Mayer, Mercer, 1943- (New York : Random House, 1983)
Malcom tries to spook his friend Bat Child at a haunted house, but his plan backfires.
"Mercer Mayer$1 (Bs little critter"--Cover.s
"A Little Critter storybook"--P. [4] of cover.
"A Green Frog Publishers, Inc./J.R. Sansevere book"--Front of t.p.
Keywords: Bats -- Fiction; Courage -- Fiction; Haunted houses -- Fiction